In silico drug re-purposing against African sleeping sickness using GlcNAc-PI de-N-acetylase as an experimental target. (December 2015) - Rashmi, Mayank; Swati, D
Graphical abstract: Abstract: Trypanosoma brucei is a protozoan that causes African sleeping sickness in humans. Many glycoconjugate compounds are present on the entire cell surface of Trypanosoma brucei to control the infectivity and survival of this pathogen. These gycoconjugates are anchored to the plasma membrane with the help of glycosyl phosphatidyl inositol (GPI) anchors. This type of anchor is much more common in protozoans than in other eukaryotes. The second step of glycosyl phosphatidyl inositol (GPI) anchor biosynthesis is catalyzed by an enzyme, which is GlcNAc-PI de- N -acetylase. GlcNAc-PI de- N -acetylase has a conserved GPI domain, which is responsible for the functionality of this enzyme. In this study, the three-dimensional structure of the target is modelled by I-TASSER and the ligand is modelled by PRODRG server. It is found that the predicted active site residues of the GPI domain are ultra-conserved for the Trypanosomatidae family. The predicted active site residues are His41, Pro42, Asp43, Asp44, Met47, Phe48, Ser74, Arg80, His103, Val144, Ser145, His147 and His150. Two hydrogen bond acceptors and four hydrogen bond donors are found in the modelled pharmacophore. All compounds of the Drugbank database and twenty three known inhibitors have been considered for structure based virtual screening. This work is focused on approved drugs because they are already tested for safety and effectiveness in humans. After the structure-based virtual screening, seventeen approved drugs and two inhibitors are found, which interact with the ligand on the basis of the designed pharmacophore. The docking has been performed for the resultant seventeen approved drugs and two known inhibitors. Two approved drugs have negative binding energy and their p K a values are similar to the selected known inhibitors. The result of this study suggests that the approved drugs Ethambutol (DB00330) and Metaraminol (DB00610) may prove useful in the treatment of African sleeping sickness.